Intercultural Competency in Public Health: A Call for Action to Incorporate Training into Public Health Education - Fleckman, Julia M.; Dal Corso, Mark; Ramirez, Shokufeh; Begalieva, Maya; Johnson, Carolyn C. (Frontiers in Public Health, 2015)
Due to increasing national diversity, programs addressing cultural competence have multiplied in U.S. medical training institutions. Although these programs share common goals for improving clinical care for patients and reducing health disparities, there is little standardization across programs. Furthermore, little progress has been made to translate cultural competency training from the clinical setting into the public health setting where the focus is on population-based health, preventative programming, and epidemiological and behavioral research. The need for culturally relevant public health programming and culturally sensitive public health research is more critical than ever. Awareness of differing cultures needs to be included in all processes of planning, implementation and evaluation. By focusing on community-based health program planning and research, cultural competence implies that it is possible for public health professionals to completely know another culture, whereas intercultural competence implies it is a dual-sided process. Public health professionals need a commitment toward intercultural competence and skills that demonstrate flexibility, openness, and self-reflection so that cultural learning is possible. In this article, the authors recommend a number of elements to develop, adapt, and strengthen intercultural competence education in public health educational institutions.